Cytomegalovirus-Specific T Cells Restricted by HLA-Cw*0702 Increase Markedly with Age and Dominate the CD8+ T-Cell Repertoire in Older People - Hosie, Louise; Pachnio, Annette; Zuo, Jianmin; Pearce, Hayden; Riddell, Stanley; Moss, Paul (Frontiers in Immunology, 2017)
Cytomegalovirus infection (CMV) elicits a strong T-cell immune response which increases further during aging in a process termed ‘memory inflation’. CMV downregulates the expression of HLA-A and HLA-B on the surface of infected cells in order to limit presentation of viral peptides to T-cells although HLA-C is relatively spared as it also engages with inhibitory KIR receptors and therefore reduces lysis by NK cells. We investigated the magnitude and functional properties of CMV-specific CD8+T-cells specific for ten peptides restricted by HLA-C in a cohort of 53 donors between the age of 23 and 91 years. This was achieved via peptide stimulation of PBMCs followed by multi-colour flow cytometry. Three peptides, derived from proteins generated in the immediate-early period of viral replication and restricted by HLA-Cw*0702, elicited strong immune responses which increased substantially with age such that the average aggregate response represented 37% of the CD8+T-cell pool within donors above 70 years of age. Remarkably, a single response represented 70% of the total CD8+T-cell pool within a 91-year old donor. HLA-Cw*0702-restricted CD8+T-cell responses were immunodominant over HLA-A and HLA-B-restricted CMV-specific responses and did not show features of exhaustion such as PD-1 or CD39 expression. Indeed such CTL exhibit a polyfunctional cytokine profile with co-expression of IFN- and TNF- and a strong cytotoxic phenotype with intracellular expression of perforin and granzymeB. Functionally, HLA-Cw*0702-restricted CTL show exceptionally high avidity for cognate peptide-HLA and demonstrate very early and efficient recognition of virally-infected cells. These observations indicate that CD8+T-cells restricted by HLA-C play an important role in the control of persistent CMV infection and could represent a novel opportunity for CD8+T-cell therapy of viral infection within immunosuppressed patients. In addition the findings provide further evidence for the importance of HLA-C-restricted T-cells in the control of chronic viral infection.